Prognostic impact of residual lateral lymph node metastasis after neoadjuvant (chemo)radiotherapy in patients with advanced low rectal cancer. Issue 6 (25th July 2019) - Akiyoshi, T.; Toda, S.; Tominaga, T.; Oba, K.; Tomizawa, K.; Hanaoka, Y.; Nagasaki, T.; Konishi, T.; Matoba, S.; Fukunaga, Y.; Ueno, M.; Kuroyanagi, H.
Abstract : Background: There is a lack of large studies focusing on the prognostic significance of lateral lymph node (LLN) metastasis following LLN dissection (LLND) in rectal cancer. The aim of this study was to evaluate the prognostic impact of LLN metastases on survival of patients with advanced low rectal cancer. Methods: Consecutive patients with locally advanced, but not metastatic, extraperitoneal rectal cancer treated with neoadjuvant (chemo)radiotherapy plus total mesorectal excision between 2004 and 2015 were included in the study. LLND was performed when pretreatment imaging documented enlarged LLNs (7 mm or greater in size). Localization of nodal metastases and long‐term outcomes were analysed. Kaplan–Meier analysis was used to compare the survival of patients with ypN0 disease with that of patients with mesorectal ypN+/LLN− status and patients with positive LLNs. The Cox proportional hazards model was used to evaluate predictors of disease‐free survival (DFS) and local recurrence. Results: A total of 613 patients were included in the study; LLND was performed in 212 patients (34·6 per cent) and 57 (9·3 per cent) had LLN metastasis. Patients with LLN metastasis had improved DFS and local recurrence cumulative incidence rates compared with patients with mesorectal ypN2+/LLN− disease (DFS: P = 0·014; local recurrence: P = 0·006). Although the DFS rate of patients with LLN metastasis was worse than that of patients with ypN0 disease ( P < 0·001), the cumulative incidence of local recurrence was similar ( P = 0·491). In multivariable analysis, residual LLN metastasis was not an independent predictor of worse DFS or local recurrence. Conclusion: LLN metastasis is not an independent predictor of local recurrence or survival. Survival of patients presenting with LLN metastasis after (chemo)radiotherapy was intermediate between that of patients with ypN0 status and those with mesorectal ypN2 positivity. Abstract : The prognostic significance of residual lateral lymph node metastasis following neoadjuvant (chemo)radiotherapy and lateral lymph node dissection in patients with advanced low rectal cancer remains unknown. This study shows that residual lateral lymph node metastasis after (chemo)radiotherapy can be considered an intermediate‐risk disease, similar to residual mesorectal ypN1 disease. Lateral nod dissection and rectal cancer Abstract : Antecedentes: No existen en la literatura grandes estudios dirigidos a investigar la importancia pronóstica de las metástasis en los ganglios linfáticos laterales ( lateral lymph nodes, LLN) después de la disección de los mismos ( LLN dissection, LLND) en pacientes con cáncer de recto. El objetivo de este estudio fue evaluar el impacto pronóstico de las metástasis en los LLN sobre la supervivencia de los pacientes con cáncer de recto. Métodos: Se analizaron 613 pacientes consecutivos con cáncer de recto localmente avanzado extraperitoneal y no metastásico tratados con (quimio)radioterapia neoadyuvante seguida de resección total del mesorrecto ( total mesorectal excision, TME) entre 2004 y 2015. Se realizó una LLND cuando el estudio mediante pruebas de imagen previo el tratamiento mostró LLN aumentados de tamaño ≥ 7 mm. Se analizó la localización de las metástasis ganglionares y los resultados a largo plazo. El análisis de supervivencia se realizó mediante el método de Kaplan‐Meier para comparar las supervivencias de los pacientes ypN0 frente a los pacientes ypN con positividad mesorrectal/LLN negativos y frente a los pacientes LLN positivos. Se utilizó el modelo de riesgo proporcional de Cox para evaluar los factores predictivos de supervivencia libre de enfermedad y de recidiva local. Resultados: Se realizó una LLND en 212 (34, 6%) pacientes, y 57 (9, 3%) pacientes presentaban metástasis en los LLN. Los pacientes con metástasis en los LLN presentaron mejores curvas de incidencia acumulada de recidiva local y de supervivencia libre de enfermedad en comparación con los pacientes con ganglios mesorrectales ypN2 positivos/LLN negativos (respectivamente, P = 0, 0135 y P = 0, 0060). Aunque la curva de la supervivencia libre de enfermedad de los pacientes con metástasis en los LLN fue peor que la de los pacientes ypN0 ( P < 0, 0001), la incidencia acumulada de recidiva local fue similar ( P = 0, 4905). En el análisis multivariable, la metástasis residual en los LLN no fue un factor predictivo independiente de peor supervivencia libre de enfermedad ni de recidiva local. Conclusión: Las metástasis en los LLN no es un factor predictivo independiente de recidiva local o supervivencia. Los pacientes que presentaron metástasis en los LLN después de (quimio)radioterapia mostraron características de supervivencia intermedias entre ypN0 y pacientes con ganglios mesorrectales ypN2 positivos.